The role of emotional intelligence and self-compassion in predicting of academic burnout with the mediating role of academic help-seeking - Fatemeh Farjam; Kazem Barzegar Bafrooei; Mehdi Rahimi (مطالعات روانشناسی تربیتی)
The aim of this study was to investigate the role of emotional intelligence and self-compassion on academic burnout mediated by academic help seeking. The present study was a descriptive and correlational study. The statistical population of this study was all undergraduate students studying in Yazd University in the academic year of 2018-2019, numbering 9022 people. Meanwhile, 368 students were selected to participate in this research by available sampling method, and in order to collect data, they used Berso's academic burnout scales (2007), self-compassion questionnaire-long form (2003), Ryan and Pintrich's help-seeking questionnaire (2012). Pearson's correlation coefficient and path analysis were also used to analyze the data. Findings showed that emotional intelligence, self-compassion and academic help-seeking have a negative and significant relationship with academic burnout at the 0.01 level. The results of path analysis also indicated that self-compassion and emotional intelligence are able to indirectly and negatively affect academic burnout through mediation of academic help-seeking. Academic help-seeking and self-compassion can also directly and negatively predict academic burnout. But emotional intelligence does not directly predict academic burnout. Overall, according to the obtained results, it can be concluded that by using self-compassion strategies, cooperative teaching methods to increase academic help-seeking capacities and self-regulation skills related to emotional intelligence, the adverse effects of academic burnout can be overcome at first, and then as Preventive strategies to prevent the occurrence of academic burnout.